THE IMPROVEMENT OF LIPID-LOWERING THERAPY EFFECTIVENESS IN PATIENTS WITH HIGH CARDIOVASCULAR RISK AND CONCOMITANT LIVER DISEASE (RESULTS OF ADDITIONAL ANALYSIS OF THE RAKURS STUDY) - N. P. Kutishenko; S. Yu. Martsevich; O. V. Lerman; I. S. Balashov; V. A. Nevzorova; I. I. Reznik; G. V. Shavkuta; D. A. Yakhontov; the working group of the RAKURS study (Столичная издательская компания, 2015)
Aim. To evaluate the differences between a group of patients treated with ursodeoxycholic acid (UDCA) during the study period and a group of patients not treated with UDCA by pseudo-randomization using Propensity Score Matching. Material and methods. 262 patients aged 60.1±8.9 years, taking statins for the secondary prevention of cardiovascular complications were included into a 6-month observational cohort study. The UDCA intake was recommended to all the patients due to the presence of liver and/or bile duct diseases. One part of the patients strictly followed medical recommendations and used UDCA, while the other part of the patients wasn't taking UDCA. This allowed comparing the effect of UDCA in these groups. Results. Propensity Score Matching method allowed forming two groups of patients of 52 people each with similar main clinical and demographic characteristics. A more significant decrease in the levels of total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) (up to 4.0 mmol/L and 1.92 mmol/L, respectively; p<0.001) after 6 months was found in patients treated with lipid-lowering therapy in combination with UDCA as compared with patients without UDCA (up to 4.52 mmol/L and 2.6 mmol/L, respectively; p<0.05). No ALT, AST, CPK, LDH activity deterioration and no bilirubin serum level increase was found. Due to statin treatment the target levels of LDL-C by the end of the study were achieved in 31% of the patients of UDCA-group. Target levels of LDL-C were not achieved in any of the patients of the group without UDCA (p<0.001). There was demonstrated a high adherence to UDCA therapy. Conclusion. Combined therapy with statins and UDCA is effective and safe in patients with high cardiovascular risk and concomitant liver disease. Co-administration of statins with UDCA is promising in the treatment of hyperlipidemia in patients with low tolerance to statins. However, additional controlled studies are required.